The application of CRISPR‐Cas for single species identification from environmental DNA. (18th July 2019) - Williams, Molly‐Ann; O'Grady, Joyce; Ball, Bernard; Carlsson, Jens; de Eyto, Elvira; McGinnity, Philip; Jennings, Eleanor; Regan, Fiona; Parle‐McDermott, Anne
Abstract: We report the first application of CRISPR‐Cas technology to single species detection from environmental DNA (eDNA). Organisms shed and excrete DNA into their environment such as in skin cells and faeces, referred to as environmental DNA (eDNA). Utilising eDNA allows noninvasive monitoring with increased specificity and sensitivity. Current methods primarily employ PCR‐based techniques to detect a given species from eDNA samples, posing a logistical challenge for on‐site monitoring and potential adaptation to biosensor devices. We have developed an alternative method; coupling isothermal amplification to a CRISPR‐Cas12a detection system. This utilises the collateral cleavage activity of Cas12a, a ribonuclease guided by a highly specific single CRISPR RNA. We used the target species Salmo salar as a proof‐of‐concept test of the specificity of the assay among closely related species and to show the assay is successful at a single temperature of 37°C with signal detection at 535 nM. The specific assay, detects at attomolar sensitivity with rapid detection rates (<2.5 hr). This approach simplifies the challenge of building a biosensor device for rapid target species detection in the field and can be easily adapted to detect any species from eDNA samples from a variety of sources enhancing the capabilities of eDNA as a tool for monitoring biodiversity.